Realization of 2.4 mm coaxial microcalorimeter system as national standard of microwave power from 1 MHz to 50 GHz. (February 2018) - Ahmad, Saood; Charles, Michael; Allal, Djamel; Negi, P.S.; Ojha, V.N
Highlights: Realization of 50 GHz microwave power standard based on thermal isolation lines. Effective efficiency is derived from electrical analysis of the isolation lines. VNA measurements to evaluate system correction factor for effective efficiency. Calorimeter provides traceable measurements with an uncertainty of 1.9% at 50 GHz. Interlaboratory comparison shows good agreement within their expanded uncertainty. Abstract: A 2.4 mm coaxial microcalorimeter system based on thermoelectric principle has been realized as a national standard of microwave power at National Physical Laboratory India (NPLI). The design is based on two symmetrical and thermally isolated transmission lines, one connected to power standard and the other connected to an identical power standard used as a thermal reference. The main function of the system is to determine the temperature variation between the two power standards, which is of the order of few milli-Kelvin, using a specially designed thermopile. The coaxial microcalorimeter along with the thermocouple power sensor will provide traceable measurements from 1 MHz to 50 GHz. An interlaboratory measurement comparison of microwave power for the validation of the 2.4 mm coaxial microcalorimeter system has been carried out between NPLI and Laboratoire National de Métrologie et d'Essais (LNE) France. The difference between the effective efficiency evaluated by the two laboratories was less than 0.5% at all frequency points. The normalized error value of NPLI for effective efficiency varies between −0.23 and +0.09 with respect to LNE. The result shows good agreement in assigning the effective efficiency to power sensor among the two labs within their claimed expanded uncertainty. It proves the degree of equivalence in measurements between two national metrology institutes (NMIs).